HUBUNGAN DIABETES MILITUS, OBESITAS DAN RIWAYAT HIPERTENSI DENGAN KEJADIAN PREEKLAMSI DI PUSKESMAS KERTAPATI - Sri Ayu Rezeki; Amlah amlah; Eka Rahmawati (Universitas Pahlawan, 2022)
Preeclampsia is a multisystem disorder with a complex etiology that typically occurs during pregnancy. Preeclampsia is usually defined as an increase in blood pressure and proteinuria that occurs after 20 weeks of gestation. In Indonesia, preeclampsia is a high cause of maternal death in addition to bleeding and infection, namely bleeding up to 28%, preeclampsia 24%, infection by 11%, complications of the uterus by 8%, prolonged labor by 5% and abortion by 5%. The purpose of this study is to determine the relationship between diabetes mellitus, obesity and history of hypertension simultaneously with the incidence of preeclampsia in the Kertapati Palembang Health Center Working Area in 2021. This type of research is quantitative using an analytical survey method with a cross sectional approach. The research was carried out at the Kertapati Health Center in Palembang with a total sample of 99 respondents. This study uses secondary data with a checklist tool. The results of the chi-square statistical test for diabetes mellitus variable obtained value (p<0.000), obesity variable obtained value (p<0.001) and hypertension history variable obtained value (p<0.001) smaller than = 0.05 indicating there is a significant relationship between diabetes mellitus, obesity and history of hypertension with preeclampsia Keywords : Diabetes Mellitus, Obesity, History of Hypertension, Preeclampsia